An Analysis Of Determination Of The Cost Of Production In Tempe Silvia Business In Semarang Urban Village Of Bengkulu City - Ramadani, Viona; Afriani , Sulisti; Fitriano , Yun (Universitas Dehasen Bengkulu, 2022)
The problem that occurs in Tempe Silvia Business is that it is still wrong in calculating the cost of production because it does not take into account factory overhead costs such as water costs, electricity costs and telephone costs in calculating the cost of production. This study aims to find out how to calculate or determine the cost of production of tempe silvia in Semarang Urban Village of Bengkulu city. The method used is descriptive quantitative using the full costing method for calculating the cost of production and determining the selling price using the full cost pricing method. The results of this study indicate that the calculation of the cost of production carried out according to the tempe silvia business in 2018 was IDR 4,178, in 2019 it was IDR 4,189, in 2020 it was IDR 4,176, and in 2021 it was IDR 4,184, so that the profit earned in 2018 of Rp. 822 per pcs, in 2019 it was IDR 811 per pcs, in 2020 it was IDR 824 per pcs, and in 2021 it was IDR 816 per pcs, with an average profit of IDR 818.25. While the calculation of the cost of production uses the full costing method in 2018 it is Rp. 4,326, in 2019 it is Rp. 4,339, in 2020 it is Rp. 4,324, and in 2021 it is Rp. 4,333, so the profit earned in 2018 is Rp. 674 per pcs, in 2019 it was IDR 661 per pcs, in 2020 it was IDR 676 per pcs, and in 2021 it was IDR 667 per pcs, with an average profit of IDR 669.5. With a profit from determining the selling price of 15%. There is a difference between the calculation of the cost of production carried out by the tempe silvia business and the calculation of the cost of production using the full costing method in 2018 the difference is IDR 148, in 2019 the difference is IDR 150, in 2020 the difference is IDR 148, in 2021 the difference is IDR Rp. 149, the difference in this calculation is due to the calculations made by Tempe Silvia not taking into account factory overhead costs.